Representasi Feminisme dalam Video “So Win”: Sebuah Analisis Wacana Multimodal - Nabilla Kusuma Vardhani; Puteri Felisha Shahnaz (JLA (Jurnal Lingua Applicata), 2026)
Feminism is one of the oldest social movements that has entered its fourth wave. This wave is closely related to the use of digital media and technology, where feminist issues are disseminated massively through various platforms, such as songs, posters, videos, and so on. One campaign video that voices feminism is "So Win" from the Nike brand. This campaign explicitly advocates feminist values, featuring various female athletes who break gender stereotypes in sports. In this study, the correlation between fourth-wave feminism and the messages conveyed through the campaign video will be discussed. To understand the messages conveyed in depth, this study uses multimodal analysis by Kress & van Leeuwen. This approach allows researchers to decipher the meaning contained not only in the narrative text, but also in visual elements such as scenes, expressions, and symbolism in the video. Furthermore, this analysis is also supported by fourth-wave feminist theory to identify how Nike's campaign reflects the characteristics of this wave, namely intersectionality, popular culture criticism, individual empowerment and visibility, and digital activism. The study's findings indicate that the visuals in the 22 scenes containing narrative text support the feminist message within them, both representationally, interactively, and compositionally. Meanwhile, elements of fourth-wave feminism are present throughout the videos, including heterogeneity within feminism, gender representation in popular culture, empowerment and visibility of individual personal experiences, and a presence in online platform.